Fine-tuning the chemical state and acidity of ceria incorporated in hierarchical zeolites for ethanol dehydration. Issue 77 (9th September 2020) - Ketkaew, Marisa; Klinyod, Sorasak; Saenluang, Kachaporn; Rodaum, Chadatip; Thivasasith, Anawat; Kidkhunthod, Pinit; Wattanakit, Chularat
Abstract : The chemical state and acidity of ceria incorporated in hierarchical zeolites have been successfully tuned due to the presence of hierarchical structures and interaction between ceria and zeolite supports with different Si/Al ratios. Abstract : The chemical state and acidity of ceria incorporated in hierarchical zeolites have been successfully tuned due to the presence of hierarchical structures of zeolite nanosheets and interaction between ceria and zeolite supports with different Si/Al ratios. The Ce reactivity of the designed materials for ethanol dehydration is remarkably improved due to the improvement of the metal–support interaction, acidity, and reducibility of Ce species, eventually facilitating an unprecedented yield of ethylene close to 100%. This finding opens up a new perspective for the development of ceria based hierarchical zeolite catalysts for ethanol dehydration applications.